Pelatihan Pembuatan Herbarium Sebagai Media Pembejalaran di Sekolah Bagi Guru MTs Dharut Tayyibin Batu Jai Kabupaten Lombok Barat - Primawati, Sri Nopita; Harisanti, Baiq Muli; Utami, Septiana Dwi; Sukri, Akhmad; Sumarjan, Sumarjan; Dewi, Ika Nurani (Jurnal Pengabdian UNDIKMA, 2021)
This community service activity aims to increase the teacher's knowledge of herbarirum learning media, and in the end the teacher can make a herbarium that can be used in the biology learning process. The main target of this dedication is biology teachers at MTs Dharut Tayyibin Batu Jai. The activity method in the form of training was then followed by making a herbarium from plants and samples brought by students from their homes or their neighborhoods. Based on the results of the evaluation and the responses of the teacher and students, they showed great enthusiasm for the activity and it was proven by the participation of students and teachers until this activity was completed. The teacher as the main target shows that their ability to make herbarium increases, the herbarium made with students can be used as biology learning that supports the learning process. The MTs students who participated in this process were very enthusiastic and active because it was such a fun new thing. It is hoped that in the future this training activity should be carried out not only in making herbariums but in making other creative learning media. The goal is to help students understand biology material and make biology lessons more fun.